2005
DOI: 10.1159/000090985
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Treatment with Exemestane and Non-Steroidal Aromatase Inhibitors in Advanced Breast Cancer

Abstract: Background: The steroidal aromatase inactivator exemestane has demonstrated activity after prior failure of non-steroidal aromatase inhibitors (including third-generation inhibitors letrozole and anastrozole) in postmenopausal women with advanced breast cancer. If exemestane is used as first anti-aromatase agent, however, it is unclear whether patients can still benefit from letrozole or anastrozole after progression. Patients and Methods: Postmenopausal patients with advanced, hormone receptor-positive or -un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 39 publications
1
32
1
1
Order By: Relevance
“…In general, objective response rates with a second-line AI are not high (0%-26%), but clinical benefit (which includes stable disease of Ն6 months' duration) is observed in 20%- 62% of patients. This effect is observed regardless of the treatment sequence: nonsteroidal AI followed by steroidal AI [48 -56] or steroidal AI followed by nonsteroidal AI [55,57]. It must be noted that these were open-label trials, many of which were single-center studies with a small number of enrolled patients, receiving a range of prior and/or concomitant therapies (e.g., chemotherapy), and at least one study used a higher dose of the second AI than is recommended [51].…”
Section: Clinical Implications Crossresistance and Sequential Therapymentioning
confidence: 99%
“…In general, objective response rates with a second-line AI are not high (0%-26%), but clinical benefit (which includes stable disease of Ն6 months' duration) is observed in 20%- 62% of patients. This effect is observed regardless of the treatment sequence: nonsteroidal AI followed by steroidal AI [48 -56] or steroidal AI followed by nonsteroidal AI [55,57]. It must be noted that these were open-label trials, many of which were single-center studies with a small number of enrolled patients, receiving a range of prior and/or concomitant therapies (e.g., chemotherapy), and at least one study used a higher dose of the second AI than is recommended [51].…”
Section: Clinical Implications Crossresistance and Sequential Therapymentioning
confidence: 99%
“…Another option for second-line endocrine treatment is fulvestrant, which has been shown to be as effective as anastrozole in patients whose disease progressed during tamoxifen treatment [67] (see above). Several studies have evaluated sequential hormone therapy and found small but consistent response regardless of the order in which therapy was administered [68][69][70]. The recently presented phase III EFECT trial evaluated sequential therapy with an AI compared to fulvestrant [66].…”
Section: Second-line Therapymentioning
confidence: 99%
“…Interestingly, patients will respond to further endocrine therapy even after their disease has progressed while on tamoxifen [73]. Little cross-resistance has been reported either between the antiestrogens and the AIs or within the group of AIs [68,70,74,75]. Use of drugs such as fulvestrant with a novel mechanism of action may also help to reduce the development of cross-resistance [76].…”
Section: Cross-resistancementioning
confidence: 99%
“…Therefore, the authors were able to conclude that objective response or durable stable disease achieved by exemestane after ns-AIs could not be explained by enhanced aromatase inhibition. Several publications have addressed this issue, showing that significant benefit can be achieved with exemestane after second-generation and third-generation non-steroidal AIs (Table 5; Geisler et al 1996, Thürlimann et al 1997, HarperWynne & Coombes 1999, Carlini et al 2001, Bertelli et al 2005, Iaffaioli et al 2005, Steele et al 2006. Furthermore, partial non-cross-resistance between steroidal and nonsteroidal AIs may be independent of the sequence employed, according to the results of a small study of sequential treatment with exemestane and non-steroidal AIs in advanced breast cancer (Bertelli et al 2005).…”
Section: Lack Of Cross-resistancementioning
confidence: 99%